Subjective Models of the Macroeconomy: Evidence from Experts and a Representative Sample - Peter Andre; Carlo Pizzinelli; Christopher Roth; Johannes Wohlfart (Center for Economic Studies and ifo Institute (CESifo), 2019)
We propose a method to measure people's subjective models of the macroeconomy. Using a sample of 2,200 households representative of the US population and a sample of more than 1,000 experts, we measure beliefs about how the unemployment rate and the inflation rate respond to four different hypothetical exogenous shocks: a monetary policy shock, a government spending shock, an income tax shock, and an oil price shock. While expert predictions are quantitatively close to benchmarks from standard DSGE models and VAR evidence and relatively homogeneous, there is strong heterogeneity among households. Households predict changes in unemployment that are largely in line with the experts' responses for all four shocks. However, their predictions of changes in inflation are at odds with those of experts both for the tax shock and the interest rate shock. We show that a substantial fraction of deviations of household predictions from expert predictions can be explained by the use of a simple heuristic according to which people expect a positive co-movement among variables they perceive as good and among variables they perceive as bad. Our findings inform the validity of central assumptions about the expectation formation process and have important implications for the optimal design of fiscal and monetary policy.
Keywords: D12; D14; D83; D84; E32; G11; 330; expectation formation; subjective models; macroeconomic shocks; monetary policy; fiscal policy